2016
DOI: 10.7759/cureus.810
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Extracorporeal Shock Wave Lithotripsy for Urolithiasis Between Children and Adults: A Single Centre Study

Abstract: ObjectiveTo retrospectively evaluate the effectiveness of extracorporeal shock wave lithotripsy (ESWL) for urolithiasis and compare the results between children and adults.Materials and methodsFrom January 2011 to January 2015 (four years), ESWL was performed in 104 children and 300 adults for urolithiasis. MODULITH® SLX-F2 lithotripter (Storz Medical AG, Tägerwilen, Switzerland) equipment was used for ESWL. The stone-free rates, the number of ESWL sessions required, complication rates and ancillary procedures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…(8,18,23) The rates of stone free after ESWL in children are considered higher than in adults and vary between 68-92%, as a result of presenting smaller and less consistent stones; they have less body volume which facilitates the transmission of the shock waves with a minimum loss of energy, greater peristalsis and distension of the ureter which facilitates passing the fragments. (5)(6)(7)13) In the current investigation the percentage of stone free patients was high just as other authors reported. However, there are authors that report lower success indexes after the first session of ESWL.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…(8,18,23) The rates of stone free after ESWL in children are considered higher than in adults and vary between 68-92%, as a result of presenting smaller and less consistent stones; they have less body volume which facilitates the transmission of the shock waves with a minimum loss of energy, greater peristalsis and distension of the ureter which facilitates passing the fragments. (5)(6)(7)13) In the current investigation the percentage of stone free patients was high just as other authors reported. However, there are authors that report lower success indexes after the first session of ESWL.…”
Section: Discussionsupporting
confidence: 75%
“…(10) Several factors influence the outcome of high ureteral stones of more than 2 cm, because they are more successful, and complications are less frequent, thus, ESWL is selected only for smaller stones. (11)(12)(13)(14) Renal localization of the lithiasis was the most frequent in this series, as other papers report, while in other series those of distal or proximal ureteral localization. (15)(16)(17)(18) We order ESWL in the child when the lithiasis is located in the inferior pole and is <1 cm just as reported by McAdams & Shukla, (19) while avoiding ESWL for stones in the middle and distal ureter because of difficulties locating them in the sacroiliac joint and to avoid possible injury to the developing organs of the reproductive system.…”
Section: Discussionsupporting
confidence: 68%
“…Within the last few decades the treatment of urinary tract stones has been revolutionized due to introduction of minimally invasive techniques. [1,2] Few decades back ureteral stones were managed by open ureterolithotomy. Then with time there was refinement of semi-rigid ureteroscopes, shock wave lithotripsy (SWL) machines, laparoscopic procedures and flexible ureterorenos-copies (URS) resulting in enormous change in the management of ureteral stones.…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing discussion about the effectiveness and safety of standard PCNL versus mini-PCNL for the management of kidney stones persists, particularly for stones larger than 2 cm [5][6][7][8]. While standard PCNL typically employs larger tract sizes (24F-30F) compared to mini-PCNL (14F-22F), the latter is not meant as a replacement for the standard PCNL technique but rather to compete with other modalities such as ECRIS, ESWL, and RIRS [9].…”
Section: Discussionmentioning
confidence: 99%